LEGAL CONSEQUENCES OF THE DETERMINATION OF THE ORIGIN OF A CHILD BORN BEFORE REMARRIAGE IN MIXED MARRIAGES TOWARD SOUTH KOREAN CITIZENSHIP RIGHTS - Naila Sativa; Anthin Lathifah; Mahdaniyal Hasanah Nuriyyatiningrum (Awang Long Law Review, 2026)
This study examines the legal consequences of the legal determination of the origin of a child born from an unregistered mixed marriage (siri) prior to the formal legalization of the marriage through tajdidun nikah (remarriage). Focusing on the Legal Determination Number 166/Pdt.P/2019/PA.Smg, the research analyzes the role of this judicial order in establishing a formal legal relationship between a child and their biological South Korean father. This relationship is a critical prerequisite for the recognition of South Korean citizenship, which strictly adheres to the ius sanguinis principle. The study employed a normative juridical research method with a case study approach. The results indicate that under Indonesian law, children born before a marriage is legally registered are categorized as being born out of wedlock; consequently, they do not automatically qualify for South Korean citizenship recognition. The research concludes that the legal determination of a child's origin in Indonesia supported by biological evidence such as DNA testing serves as a mandatory legal bridge to prove the lineage required to satisfy foreign citizenship requirements and ensure the child's legal protection.